Clinical and radiographic analysis of an endodontic paste based on calcium hydroxide and Aloe vera: randomized clinical trial (Research, Society and Development, 2021)
This randomized clinical trial evaluated an intracanal medicinal paste based on Ca(OH)2 and Aloe vera in necrotic teeth with periapical lesions. Sixty-four teeth, from 60 patients, were divided according to the intracanal medication used: Control (Ca(OH)2 and saline solution), and experimental (Ca(OH)2 and Aloe vera). Endodontic instrumentation and insertion of intracanal medication were performed according to the group. After 15 days, the teeth were filled and restored. Postoperative symptoms were assessed following a pain scale. Clinical and radiographic evaluation was performed at three, six and nine months after treatment. Treatments were classified into success (those with partial or complete healing) and failure. For statistical analysis of postoperative pain between groups, the Mann-Whitney test was used. The intragroup analysis used the Friedmann test. To assess treatment success, the chi-square test was used. It was considered significant p